2022
DOI: 10.1111/ajo.13617
|View full text |Cite
|
Sign up to set email alerts
|

Australian medical students’ and junior doctors' perceptions of gender discrepancies in obstetrics and gynaecology

Abstract: Background There is currently a gender imbalance 85:15 female/male in the intake into specialist training for the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG). Aims To determine the views and perceptions of Australian medical students, and junior doctors in the first five years of practice, toward obstetrics and gynaecology (O&G) as a career, including whether there are any perceived barriers to the pursuit of such a career. Materials and Methods A semi‐structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
(19 reference statements)
2
5
0
Order By: Relevance
“…Surviving birth suite as a medical student traditionally is regarded as a rite of passage, but evidence points to discrimination and bias being a common experience for undergraduate and prevocational students in obstetrics and gynaecology, particularly on delivery units, with males impacted disproportionately according to findings Kyaw et al 1 reported in this ANZJOG issue, corroborating previous studies. [2][3][4][5] A career in obstetrics and gynaecology (O & G) is not that appealing, even less so for men, representing fewer than 20% in RANZCOG (Royal Australian and New Zealand College of Obstetricians and Gynaecologists) specialist training, and only 35% of general practitioners undertaking the advanced RANZCOG diploma.…”
Section: Fewer Men Choosing An Obstetrics and Gynaecology Careersupporting
confidence: 83%
See 4 more Smart Citations
“…Surviving birth suite as a medical student traditionally is regarded as a rite of passage, but evidence points to discrimination and bias being a common experience for undergraduate and prevocational students in obstetrics and gynaecology, particularly on delivery units, with males impacted disproportionately according to findings Kyaw et al 1 reported in this ANZJOG issue, corroborating previous studies. [2][3][4][5] A career in obstetrics and gynaecology (O & G) is not that appealing, even less so for men, representing fewer than 20% in RANZCOG (Royal Australian and New Zealand College of Obstetricians and Gynaecologists) specialist training, and only 35% of general practitioners undertaking the advanced RANZCOG diploma.…”
Section: Fewer Men Choosing An Obstetrics and Gynaecology Careersupporting
confidence: 83%
“…Surviving birth suite as a medical student traditionally is regarded as a rite of passage, but evidence points to discrimination and bias being a common experience for undergraduate and prevocational students in obstetrics and gynaecology, particularly on delivery units, with males impacted disproportionately according to findings Kyaw et al 1 . reported in this ANZJOG issue, corroborating previous studies 2–5 .…”
supporting
confidence: 83%
See 3 more Smart Citations